Impact of transformational leadership on maritime performance and satisfaction: Maritime education perspectives - Damoyanto Purba (Universitas Muhammadiyah Malang, 2025)
This study examines how transformational leadership impacts port performance and job satisfaction in the maritime sector, aiming to shed light on effective leadership strategies and their implications for organizational outcomes. Using qualitative approaches such as in-depth interviews and focus groups, the study gathered data from maritime cadets and industry professionals to investigate their perceptions and experiences regarding transformational leadership, port performance, and job satisfaction. The study demonstrates a strong correlation between transformational leadership traits and global standards, emphasising the importance of visionary, inspiring, and empowering leadership qualities in enhancing organizational performance. While port performance and job satisfaction were generally rated positively, deviations from international benchmarks suggest areas for improvement. This research enhances our understanding of leadership dynamics and organizational outcomes in maritime operations, offering practical insights for industry stakeholders. It underscores the significance of aligning leadership practices with international standards to improve effectiveness. The study suggests the need for leadership development programmes, standardised performance metrics, and employee-focused policies to boost organisational effectiveness and human resource management in the maritime sector.